Formulation and Characterization of a Pluronic F127 Polymeric Micelle as a Nanocarrier for Berberine Delivery - Noora Kadhim Hadi Alyasari; Anwar Jasib Almzaiel (Indonesian Journal of Chemistry, 2024)
Berberine's (Ber’s) lower water solubility, which leads to low bioavailability, poses substantial delivery-related barriers to its therapeutic efficacy. Thus, a new approach to improving Ber's delivery and bioavailability is required. In this study, a Pluronic F127 micelle containing Ber (mBer) was formulated using thin-film hydration technique with the intention of resolving challenging issues associated with Ber delivery. The micelle was tested for drug loading and retention efficiency, size, zeta potential, shape, in vitro release, and in vitro toxicity. The spherical micelles that were made had an average encapsulation efficiency of 85%, a hydrodynamic size of 82.2 nm, a polydispersity of 0.176, and a zeta potential of −47.4 mV. The results of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) indicated that Ber was physically entrapped and in an amorphous state within the synthesized micelles. Compared to the free Ber solution, the in vitro release of Ber from micelles exhibited both short-term rapid release and sustained release. The mBer was shown to be relatively non-toxic to blood cells via an in vitro hemolysis assay. Our findings showed that polymeric F127 micelles could be a simple nanocarrier for Ber delivery, which can be used to enhance the therapeutic efficiency of Ber.